2018
DOI: 10.4194/1303-2712-v18_4_15
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The present study was aimed at determining the effects of medicinal herbs adjuvants on growth, hematoebiochemical parameters, some non-specific immunity and disease resistance to Photobacterium damselae in Sobaity sea bream (Sparidentex hasta). The fish (mean body weight 3.08±0.31 g) were fed fishmeal diets supplemented with either 1% of Garlic (Allium sativum), 1% supplemented of Ginger (Zingiber officinale), 1% supplemented of thyme (Thymus vulgaris), a mixture of these herbs (1% Garlic + 1% Ginger + 1% thym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 56 publications
2
10
0
Order By: Relevance
“…The findings of the present study on growth performances and feed utilization revealed that C. gariepinus fry fed with basal diet supplemented with either garlic powder or ginger powder showed better growth and feed utilization in term of weight gain, length gain, specific growth rate, feed intake, feed conversion ratio as well as protein efficiency ratio compared to control diet. On contrary to the results obtained by Mahmoud et al [27] who found poor growth and feed utilization in term of specific growth rate and feed conversion ratio after feeding Oreochromis niloticus fingerlings for 60 days with 1.5% ginger and garlic compared to basal control diet, the results of the present study are in accordance with those obtained by Jahanjoo et al [44] who recorded better growth performance and feed utilization in Sobaity Sea Bream (Sparidentex hasta) fry fed with basal diet containing 1% of garlic and ginger respectively for 8 weeks. In addition, the highest values of growth performance and feed utilization were observed in fish fry fed the basal diet containing 1% of both ginger and garlic compared to control diet and even diet with 2% of plant material.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The findings of the present study on growth performances and feed utilization revealed that C. gariepinus fry fed with basal diet supplemented with either garlic powder or ginger powder showed better growth and feed utilization in term of weight gain, length gain, specific growth rate, feed intake, feed conversion ratio as well as protein efficiency ratio compared to control diet. On contrary to the results obtained by Mahmoud et al [27] who found poor growth and feed utilization in term of specific growth rate and feed conversion ratio after feeding Oreochromis niloticus fingerlings for 60 days with 1.5% ginger and garlic compared to basal control diet, the results of the present study are in accordance with those obtained by Jahanjoo et al [44] who recorded better growth performance and feed utilization in Sobaity Sea Bream (Sparidentex hasta) fry fed with basal diet containing 1% of garlic and ginger respectively for 8 weeks. In addition, the highest values of growth performance and feed utilization were observed in fish fry fed the basal diet containing 1% of both ginger and garlic compared to control diet and even diet with 2% of plant material.…”
Section: Discussionsupporting
confidence: 87%
“…These results are in contradiction with those reported by Mahmoud et al [27] who found no significant difference between the growth performance and feed utilization of O. niloticus fingerlings fed on diet containing 1.5% ginger and garlic during 60 consecutive days. In addition, Jahanjoo et al [44] after feeding Sobaity Sea Bream (Sparidentex hasta) fry with basal diet containing 1% of garlic and ginger respectively reported better growth performance and feed utilization. Sahu et al [48] also showed that feed conversion ratio and specific growth rate were not significantly influenced in Labeo rohita fed on diet containing 0.5% and 1% garlic inclusion.…”
Section: Discussionmentioning
confidence: 98%
“…Such an elevation might have resulted in causing lipid peroxidation inhibition in the ginger-fed groups, with the most prominent being observed in the GP15 group. Authors have reported high activity of SOD in sobaity sea bream Sparidentex hasta when fed with diets supplemented with 0.1 g ginger kg −1 of feed ( Jahanjoo et al, 2018 ). In another study on C. carpio , feeding of a diet supplemented with ginger extract at a dose of 2 g·kg −1 caused a significant improvement in the SOD activity ( Mohammadi et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Jahanjoo et al [76] showed that serum lysozyme activity, total Ig, and ACH50 activity significantly increased in fish fed a mixture of three medicinal herbs and ginger. The immune system is stimulated by synbiotic Biomin ® IMBO and increases the proliferation of macrophages, growth, survival of fish, and the volume of beneficial bacteria in the gut, affecting the composition of the body [77].…”
Section: Discussionmentioning
confidence: 99%